Independent predictors of long-COVID in patients without comorbidities. Data from the Polish long-COVID cardiovascular (PoLoCOV-CVD) study. (3rd October 2022) - Chudzik, M; Banach, M; Lewek, J; Kapusta, J; Bielecka-Dabrowa, A; Jankowski, P
Abstract: : Coronavirus disease 2019 (COVID-19) is a serious respiratory disease that results from infection with a newly discovered coronavirus (SARS-COV-2). Patients recovering from SARS-COV2 infection complain of persisting symptoms which may lead to chronic fatigue syndrome and as well as many other complications. The vast majority of COVID-19 patients remaining in isolation/quarantine, due to the mild course of the disease, do not require hospitalization. There are many studies describing the course and complications of patients hospitalized due to COVID-19. There is little published data on how nonhospitalized patients get sick and what are the early and late complications of SARS-CoV-2 infection. Little is also known about Long-COVID (LC) in patients without comorbidities. Therefore, the aim of our analysis was to assess the predictors of long-lasting symptoms in patients without comorbidities suffering from COVID-19. Methods: Patients ≥18 years of age diagnosed with COVID-19, were examined after full recovery (resolution of clinical symptoms, minimum 14 days after last symptoms). Patient information, course of the disease with symptoms, post-COVID-19 complaints were collected within 4–8 weeks after the COVID-19 recovery. We followed patients for at least 3 months. Patients were ordered the following tests: 12-lead ECG, 24-hour Holter ECG monitoring, 24-hour Holter blood pressure monitoring, Echocardiographic of the Heart assessment, Biochemical tests: lipid profile, glucose or glycosylated hemoglobin level, D-dimers. In patients with indications, the following were additionally performed: Magnetic resonance imaging of the heart, Computed tomography angiography (CTA) of pulmonary vessels, Angio CT of coronary vessels or other diagnostic tests. Results: We identified 701 consecutive patients without comorbidities of whom 488 pts completed 3 month follow-up. Comparisons were made between LC group (n=218) and non-LC group (n=270). The demographic and laboratory characteristics of the studied group are presented in Table 1. Patients with severe course of acute phase of COVID-19 developed LC more often (72 vs. 28%, p<0.001). Significant differences regarding sex, weight, height, body mass index were observed. Patients with LC more often presented with dyspnoea, significant fatigue, chest pain, leg muscle pain, headache, arthralgia and chills. No statistically significant difference was observed regarding laboratory tests, 24-hour systolic and diastolic BP and echocardiographic parameters. LC group had higher 24-hour heart rate (77 [72–83] vs. 75 [70–81], p=0.021). Multivariate regression analysis showed that LC patients had higher BMI (odds ratio 1.057, 95% confidence intervals 1.016–1.100) and almost twice as often had a severe course (1.736, 1.071–2.814) and presented with arthralgia in the acute phase (1.901, 1.225–2.950). Conclusions: Severe course of COVID-19, BMI, and arthralgia are independently related to long-COVID in patients without comorbidities. Funding Acknowledgement: Type of funding sources: None.